Trends in Capital Market Research and Taxation Policy in Indonesia: A Bibliometric Analysis of the Literature from 2000 to 2025 - Wahyudi Wahyudi; Syarifuddin Syarifuddin; Syarifuddin Rasyid (Jurnal Riset Perpajakan: Amnesty, 2025)
This study examines the evolution of research on capital markets and taxation policy in Indonesia from 2000 to 2025 using a comprehensive bibliometric approach. Data were extracted from Scopus and Web of Science and analyzed using Bibliometrix (R) and VOSviewer to assess scientific productivity, citation structures, keyword networks, and thematic development. A total of 609 documents and 53,971 citations were identified, indicating substantial growth in scholarly attention across four phases: initiation (2000–2004), consolidation (2005–2014), explosion (2015–2021), and normalization (2022–2025). Publication output peaked in 2021, whereas citation-per-article declined in recent years, reflecting citation dilution as publication volume increased. World Development emerged as the most productive source, while The Quarterly Journal of Economics showed the highest citation intensity. Seminal works by Gabaix et al. (2003), Chan, Covrig & Ng (2005), and Johnson et al. (2000) formed the intellectual core driving research development. Keyword mapping revealed “stock exchange,” “tax incentive,” and “earnings management” as basic themes, while the “tax authority–fiscal policy” cluster appeared as a motor theme with high relevance and strong development. Thematic evolution indicates a shift from macro-level concerns—market infrastructure and fiscal incentives—toward micro-level issues such as asymmetric information, governance, and tax reform effectiveness. Findings highlight the need for methodological advancement through machine learning, natural experiments, and greater use of domestic micro-data to enhance theoretical contributions and strengthen policy relevance in Indonesia’s capital market and taxation research landscape.